1997
DOI: 10.1007/s002030050537
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of 9-hexadecenoic acid cis-trans isomerase from Pseudomonas sp. strain E-3

Abstract: A 9-hexadecenoic acid cis-trans isomerase (9-isomerase) that catalyzed the cis-to-trans isomerization of the double bond of free 9-cis-hexadecenoic acid [16:1(9c)] was purified to homogeneity from an extract of Pseudomonas sp. strain E-3 and characterized. Electrophoresis of the purified enzyme on both incompletely denaturing and denaturing polyacrylamide gels yielded a single band of a protein with a molecular mass of 80 kDa, suggesting that the isomerase is a monomeric protein of 80 kDa. The 9-isomerase, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The enzyme has been purified (49,50), and the encoding gene was cloned and sequenced (24,27). It has been verified that the isomerization reaction is possible without growth (22,36).…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme has been purified (49,50), and the encoding gene was cloned and sequenced (24,27). It has been verified that the isomerization reaction is possible without growth (22,36).…”
Section: Resultsmentioning
confidence: 99%
“…16,23,24) However, in growing cells of Pseudomonas strains 16,23) both changes of the saturation degree of the fatty acids by de novo synthesis of saturated and unsaturated fatty acids via the anaerobic pathway 25,26) and conversion of cis into trans fatty acids by a cis-trans isomerase 27) can occur in parallel. Therefore the elucidation of their contribution to homeoviscousis is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme has been purified from the periplasmic fraction of Pseudomonas oleovorans (17) and Pseudomonas sp. strain E3 (16) and has been isolated as a His-tagged P. putida P8 protein heterologously expressed in Escherichia coli (9). The cis-trans isomerase gene cloned and sequenced from P. putida P8 (10,21) and P. putida DOT-T1E (12) made evident that the isomerase has an N-terminal hydrophobic signal sequence, which is cleaved off after the enzyme has been targeted to the periplasmic space.…”
mentioning
confidence: 99%
“…For an enzyme preparation from Pseudomonas sp. strain E3, which is presumably homologous to the cti gene product of P. putida P8, it was suggested that iron (probably Fe 3ϩ ) plays a crucial role in the catalytic reaction (16). Despite the wealth of available information, the biochemical mechanism of the solvent-induced regulation of isomerase activity, in relation to membrane homeostasis (18), still remains obscure.…”
mentioning
confidence: 99%
See 1 more Smart Citation